Flow Cytometry‐Based Quantification of Cell Proliferation in the Mixed Cell Co‐Culture. Issue 1 (1st January 2013) - Gerashchenko, Bogdan I.; Howell, Roger W.
Abstract: In cell communities, among the crucial signals that govern cell function are those generated locally by surrounding cells. A co‐culture of mixed homotypic or heterotypic cells, which is often used in various fields of experimental biology and medicine, can be applied for elucidation of the role of cell proximity in modulating proliferative responses. Quick and reliable quantification of the changes in proliferation of each of the mixed cell populations as a result of their co‐culture is of importance. For this purpose, flow cytometry together with fluorescent tracers that do not affect cell proliferation can be used. Curr. Protoc. Cytom . 63:9.40.1‐9.40.10. © 2013 by John Wiley & Sons, Inc.